2005
DOI: 10.1099/mic.0.28056-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of two CbbRs in the transcriptional regulation of three ribulose-1,5-bisphosphate carboxylase/oxygenase genes in Hydrogenovibrio marinus strain MH-110

Abstract: Hydrogenovibrio marinus MH-110 possesses three different sets of genes for ribulose 1,5-bisphosphate carboxylase/oxygenase (RubisCO): two form I (cbbLS-1 and cbbLS-2) and one form II (cbbM). We have previously shown that the expression of these RubisCO genes is dependent on the ambient CO 2 concentration. LysR-type transcriptional regulators, designated CbbR1 and CbbRm, are encoded upstream of the cbbLS-1 and cbbM genes, respectively. In this study, we revealed by gel shift assay that CbbR1 and CbbRm bind with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…We thus propose that orf12 (LysR1 homolog) activates cbbM transcription. However, Toyoda et al (2005) suggested that in H. marinus transcriptional regulators of the lysR family, namely CbbR1 and CbbRm, were required to activate the expression of cbbLS-1 and cbbM, respectively, which in our case only holds true for orf12 (LysR1 homolog) and cbbM. More experiments will be needed to better understand the interaction and interconnection between LysR regulators and the structural RubisCOs.…”
Section: The Effect Of Gene Deletions Outside Of the Rubisco Gene Clumentioning
confidence: 91%
See 2 more Smart Citations
“…We thus propose that orf12 (LysR1 homolog) activates cbbM transcription. However, Toyoda et al (2005) suggested that in H. marinus transcriptional regulators of the lysR family, namely CbbR1 and CbbRm, were required to activate the expression of cbbLS-1 and cbbM, respectively, which in our case only holds true for orf12 (LysR1 homolog) and cbbM. More experiments will be needed to better understand the interaction and interconnection between LysR regulators and the structural RubisCOs.…”
Section: The Effect Of Gene Deletions Outside Of the Rubisco Gene Clumentioning
confidence: 91%
“…Despite RubisCO activity loss, none of these four enzymes have ever been linked to the expression of a fully functional RubisCO and current annotations do not imply that these genes encode functions associated with RubisCO regulation, assembling or activation mechanisms. However, the significant RubisCO activity loss may be explained if gene products interplay with RubisCO-associated genes encoded on the entire metagenomic fragment or if the activity of encoded enzymes has an impact on intercellular conditions such as CO 2 concentrations, pH values or ATP/ADP ratio, which are important to maximize RubisCO activity (Portis, 1990;Toyoda et al, 2005) and which might be applicable in heterologous hosts like E. coli as well.…”
Section: The Effect Of Gene Deletions Outside Of the Rubisco Gene Clumentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodobacter capsulatus also presents an interesting situation where this organism contains two cbbR genes encoding two distinct CbbR proteins (CbbR I and CbbR II ) that regulate two separate cbb operons, one of which, along with its cognate cbbR gene, was apparently derived from a chemoautotrophic ancestor (7,28). In the chemoautotroph Hydrogenovibrio marinus, there also are two cbbR genes (cbbR1 and cbbRm) and three cbb operons (cbbLS-1, cbbLS-2, and cbbM), with cbbR1 located upstream and in an orientation opposite that of cbbLS-1, while the cbbRm gene is located upstream of but in the same orientation as cbbM (10,(29)(30)(31). The cbbLS-2 operon contains genes encoding carboxysomes and is expressed under conditions of low CO 2 concentrations, independently of CbbR1 or CbbRm regulation (30,31).…”
Section: Cbbr and Cbb Gene Organizationmentioning
confidence: 99%
“…CbbR-dependent regulation occurs in diverse organisms, including nonsulfur and sulfur purple bacteria, marine and freshwater chemoautotrophic bacteria, cyanobacteria, methylotrophic bacteria, several varieties of hydrogen-oxidizing bacteria, and different Pseudomonas, Mycobacterium, and Clostridium strains (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In addition, CbbR regulates carbon fixation gene expression in chloroplasts of eukaryotic red algae (15).…”
mentioning
confidence: 99%